STUDI KUANTITATIF PENYEBAB OBESITAS SENTRAL PADA REMAJA - Noorma, Nilam; Siswoko, Siswoko; Syam, Mayrita; Rotinsulu, Ria Angelina Jessica (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Central obesity or abdominal obesity is a condition characterized by excessive fat accumulation localized in the abdominal area, particularly in the intra-abdominal fat tissue. Based on the results of a preliminary study on the incidence of central obesity among students in several high schools in Semarang, a total of 10 respondents were obtained. The measurement results showed that most of the students studied had central obesity. In detail, 9 students or about 90% of the total respondents in grade X were classified as having central obesity based on waist circumference indicators. The purpose of this study was to analyze the causes of central obesity in adolescents. The research design used in this study was cross-sectional. The research was conducted in several high schools in Semarang City. The research was conducted in July 2025. The research population consisted of all tenth-grade students in several high schools in Semarang City. The sample consisted of 55 tenth-grade students. The sampling technique used was accidental sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between excess nutrition (p value: 0.000) and body fat percentage (p value: 0.000) with the incidence of central obesity in adolescents. Respondents were advised to pay more attention to consumption recommendations in accordance with health standards. It is important for adolescents to limit their sugar consumption, given the risk of obesity and diabetes that can arise from a young age. Salt consumption should also be reduced to maintain heart health and prevent high blood pressure in the future. Keywords: Overweight, Adolescents, Obesity